MAiD, Mental Disorder, and Capacity: Recognizing the Complexity of Moral Agency in Capacity Assessment - Barbour, Kyle (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2025)
Medical assistance in dying (MAiD) has become a prominent form of end-of-life care within the Canadian health system, yet it is not without its critics. Drawing even more critical attention is the possibility of Canada expanding MAiD eligibility to persons who suffer from mental disorder as their sole underlying medical condition (MAiD MD-SUMC). Unlike physical conditions that cause pain and suffering, mental disorder has the intrinsic potential to affect one’s ability to understand and appropriately value the consequences of one’s actions and decisions. There is thus a significant risk that a patient who has requested MAiD MD-SUMC may be unable to provide valid consent due to an impaired ability to either: 1) adequately understand the consequences of receiving MAiD or 2) place that consequence within a consistent set of values. Due to the important ways in which mental disorder can affect one’s values and desires, this paper argues that we must evaluate decision-making capacity in a more holistic way that includes both cognitive and evaluative factors. My argument is based upon a presentation of the evaluative factors involved in decision-making, a demonstration that these factors may be significantly affected by mental illness, and a suggestion that we require more holistic criteria for capacity evaluation than the excessively cognitive criteria espoused by most commonly used assessment tools. Because of the interplay between these aspects of my argument and the extremely high stakes involved in MAiD assessments, I suggest that capacity evaluations (both in general and especially for MAiD requests) ought to incorporate an aspect of narrative assessment by which the patient’s values and self-understanding can be better assessed.